Ogallala Aquifer Program: A Catalyst for Research and Education to Sustain the Ogallala Aquifer on the Southern High Plains (2003–2017). (28th December 2017) - Brauer, David; Devlin, Dan; Wagner, Kevin; Ballou, Mike; Hawkins, Dean; Lascano, Robert
Abstract: The Ogallala Aquifer Program (OAP) was created in 2003 with support from Congressmen from Kansas and Texas. The OAP is a research‐education consortium seeking solutions from problems arising from declining water availability from the Ogallala Aquifer in western Kansas and the Texas High Plains. The consortium is led by the Agricultural Research Service (ARS) laboratories in Bushland and Lubbock, TX, and the university partners are Kansas State University, Texas A&M AgriLife Research and Extension Service, Texas Tech University, and West Texas A&M University. The OAP has provided over $40 million to support research and education activities. About half of these funds were used to support permanent ARS scientists and ARS hired post‐docs. The other half were used by university scientists to supplement on‐going projects by providing support for supplies, sample analyses, temporary employees, etc. Initially, OAP activities were focused on seven priorities. In 2013, four objectives replaced the original seven priorities. A fifth priority was added in 2017. The current objectives are: 1) Develop and evaluate water management strategies and technologies that could reduce water withdrawals for irrigation by 20% in 2020 compared to 2012; 2) Develop and evaluate management strategies and technologies that would increase the productivity and profitability of dryland cropping systems; 3) Improve the understanding of hydrological and climatic factors that affect water use and agricultural profitability; 4) Determine the impacts of alternative water withdrawal/use policies on the economic viability of the agriculture industry of the Southern Ogallala Aquifer Region; and 5) Develop best management practices for production of high value and alternative crops for both dryland and irrigated systems. The objectives of the program and distribution of resources are decided by an executive committee with a member from each of the four universities, two from ARS, one from Bushland, and the other from Lubbock. Proposed projects that utilize resources from more than one participating institution, leverage existing resources, and address the stated objectives are more likely to be provided support. The impact of the OAP on research directed at agriculture on the High Plains has been recognized by three prestigious awards.